A second chance at education for early school leavers - Cain Polidano; Domenico Tabasso; Yi-Ping Tseng (Institute for the Study of Labor (IZA), 2012)
Despite efforts to engage youth in education, there have been only modest improvements in the rates of school completion across OECD countries since the mid-1990s. These modest improvements underline the importance of programs that encourage early school leavers to return to post-school education. The objective of this paper is to better understand the factors that affect the chances of re-engaging early school leavers in education, with a particular focus on the importance of time out from school (duration dependence) and school-related factors. Using data from three cohorts of the Longitudinal Survey of Australian Youth and duration models that control for unobserved heterogeneity, our results suggest that programs that encourage an early return to study and programs that develop post-school career plans may be more effective than programs that concentrate on improving numeracy and literacy scores.
Keywords: I20; J01; 330; educational economics; demand for schooling; human capital; Jugendliche; Abbrecher; Bildungsverhalten; Erwachsenenbildung; Schulbesuch; Australien